2020
DOI: 10.1155/2020/8163839
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Huaier on Melanoma Invasion, Metastasis, and Angiogenesis

Abstract: Malignant melanoma (MM) is a highly metastatic and malignant cancer. Developing potential drugs with good efficacy and low toxicity for MM treatment is needed. Huaier, extracted from the mushroom Trametes robiniophila Murr, has been widely used in clinical anticancer treatments in China. A previous work done by our group confirmed that Huaier could inhibit cell proliferation and induce apoptosis in human melanoma cells. The current study is aimed at investigating the effects of Huaier on melanoma metastasis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(23 reference statements)
1
3
0
Order By: Relevance
“…27 Huaier also exhibits antitumor and antimetastatic activities in malignant melanoma, and it inhibits the epithelial-mesenchymal transition by suppressing HIF-1/VEGF and AEG-1 signaling pathways. 28 In the present work, we revealed the function of Huaier in CSCC, showing that Huaier repressed the proliferation, migration, and invasion of CSCC cells. In addition, inhibition of CDKN2A or TP53 reversed the influence of Huaier treatment on proliferation, migration, and invasion of CSCC cells.…”
Section: Discussionsupporting
confidence: 49%
“…27 Huaier also exhibits antitumor and antimetastatic activities in malignant melanoma, and it inhibits the epithelial-mesenchymal transition by suppressing HIF-1/VEGF and AEG-1 signaling pathways. 28 In the present work, we revealed the function of Huaier in CSCC, showing that Huaier repressed the proliferation, migration, and invasion of CSCC cells. In addition, inhibition of CDKN2A or TP53 reversed the influence of Huaier treatment on proliferation, migration, and invasion of CSCC cells.…”
Section: Discussionsupporting
confidence: 49%
“…Animal experiments provide strong evidence to the safety of Huaier. Various aspects of Huaier-treated animals that could indicate possible toxicity, such as body weight ( 22 , 31 , 34 , 90 , 119 122 ), behavior ( 21 , 30 , 123 ), appetite and food intake ( 112 , 124 ), histology of major organs (heart, liver, kidney, lungs, spleen, pancreas and brain) ( 17 , 20 , 32 , 33 , 125 ), blood assay ( 20 , 23 ), liver and kidney function ( 29 ), and animal survival ( 112 ), have been thoroughly examined in numerous studies. However, almost all of these studies reported negligible signs of toxicity in animals, indicating the safety of Huaier in preclinical studies.…”
Section: Toxicitymentioning
confidence: 99%
“…Huaier extract significantly inhibits A375 cell metastasis at concentrations ranging from 4-16 mg/ml, in vitro and in vivo. In addition, Huaier extract possesses an antimetastasis effect through HIF-1α/VEGF and AEG-1 signaling pathways and inhibition of the epithelial-mesenchymal transition (EMT) by downregulating hypoxia-inducible factor-1α (HIF-1α), vascular endothelial growth factor (VEGF), astrocyte-elevated gene-1 (AEG-1), and N-cadherin expression, whereas upregulating E.-cadherin expression in A375 cells and tumor tissue (Su et al, 2020). The anticancer effect of Huaier extract has been confirmed in liver, lung, breast, ovarian, gastric, and prostate cancer .…”
Section: Trametes Robiniophila Murrmentioning
confidence: 99%